2020
DOI: 10.1001/jamaneurol.2020.0825
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Major Neurological Complications From Vein of Galen Malformation Embolization

Abstract: IMPORTANCEMajor neurological complications from the embolization of vein of Galen malformations (VOGMs) are poorly understood. We provide a detailed analysis of contributors to periprocedural neurological complications and lessons learned.OBJECTIVE To assess the rate of major periprocedural neurological complications following VOGM embolization with major procedural and strategic contributors. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study was conducted at a quarternary referral pediatric hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 18 publications
1
25
2
2
Order By: Relevance
“…Endovascular embolization of VOGM is the standard treatment methodology; however, up to one third of patients will suffer major neurologic morbidity or mortality. [2][3][4][5] A recent metanalysis demonstrated that 19% of cases may have technical complications with complete embolization occurring in only 56% of cases. 2 Even with modern endovascular devices, technical complications such as arterial perforation and off target embolization continue to occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endovascular embolization of VOGM is the standard treatment methodology; however, up to one third of patients will suffer major neurologic morbidity or mortality. [2][3][4][5] A recent metanalysis demonstrated that 19% of cases may have technical complications with complete embolization occurring in only 56% of cases. 2 Even with modern endovascular devices, technical complications such as arterial perforation and off target embolization continue to occur.…”
Section: Discussionmentioning
confidence: 99%
“…2 Even with modern endovascular devices, technical complications such as arterial perforation and off target embolization continue to occur. 3,6,7 This case describes the technical safety of a novel dual lumen balloon microcatheter resulting in the angiographic cure of a VOGM. In the setting of a high flow shunt such as these lesions, a small dual lumen balloon with the ability to tolerate liquid embolic is extremely advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 However, some authors concluded that the presence of normal deep venous drainage into the venous sac of the VGAM, excessive embolization of the venous outflow, treatment of more proximal fistulae before treating distal fistulae, and the use of larger microcatheters in neonates can contribute to an unexpected outcome. 12 It is important to consider that despite the technological evolution leading to early diagnosis and more favorable treatments, the prognosis of these patients remains associated with their clinical conditions at birth. 10…”
Section: Discussionmentioning
confidence: 99%